Measurement of Carbon Dioxide Emission Level at Urban Intersections in Bandar Maharani Muar - Zaihannuddin, Muhammad Izzuddin; Azizan, Muhammad Fauzan; Nawawie, Nur Anis Amiera (Multidisciplinary Applied Research and Innovation, 2023)
The amount of carbon dioxide emissions, which is one of the most dangerous greenhouse gasses, is getting worsen nowadays. Increasing amount of traffic on roads might be one the main contributing factors.  The aim of this study is to analyse the measurement of carbon dioxide emission level at urban intersections in Bandar Maharani, Muar. Therefore, the objectives that need to be fulfilled are to measure the emission of carbon dioxide at urban signalized intersection and to determine correlation between carbon dioxide emission and intersection’s measure of effectiveness parameters such as degree of saturation, delay, and queue distance.  Data were collected from secondary data that was taken from previous Final Year Project. The data were then analysed using SIDRA Intersection 8.0.  The outcomes were obtained from the output of carbon dioxide emission model and tabulated to the Microsoft Excel for statistical analysis. Other outcomes from all intersections such as degree of saturation, delay and queue distance were used to determine the correlation with cardon dioxide emission. Based on the analysis, each intersection produces different amount of carbon dioxide. the highest emission of carbon dioxide was recorded at intersection 006, while the least amount of the carbon dioxide emission was recorded at intersection 005.  The values of correlation coefficient obtained shows that the relationship is a strong linear relationship between carbon dioxide emission and all parameters.  In conclusion, the higher the degree of saturation, delay and queue distance of intersection, the higher its carbon dioxide emission produce. Therefore, intervention to reduce the emission of carbon dioxide should be implemented in order to develop a low carbon district.